PENERAPAN POSISI SEMI FOWLER TERHADAP KETIDAKEFEKTIFAN POLA NAFAS PADA PASIEN CONGESTIVE HEART FAILURE (CHF) - Ahmad Muzaki, Yuli Ani (AKPER Pemkab Purworejo, 2020)
Congestive Heart Failure or more commonly known as Heart failure is a disease of clinical syndrome that is characterized by shortness of breath and fatique at rest or during activities caused by structural abnormalities or heart function. CHF patients with ineffective breathing patterns need to be given a semifowler position. Objective: is given this position to decrease oxygen consumption and increase maximal lung expansion, so the ineffectiveness of the client breathing pattern is more optimal CHF patients at RSUD Wates. Method: This type of research is descriptive using case study approach method. Subjects in this case study were two patients who had CHF patient with ineffective breathing pattern. Semifowler interventions is given where the position of the head and body is increased with declivity 45°. Results: The application of semi-fowler position (sitting position 45 °) for 3x24 hours in accordance with the SOP helps reduce shortness of breath and helps optimize RR on the client so that the problem of ineffective breathing patterns can be overcome. Conclusion: Significant sleep angle adjustment interventions can produce good respiration, so it can be considered as one of the interventions to maximize the ineffectiveness of breathing patterns.